2017
DOI: 10.18632/oncotarget.15639
|View full text |Cite
|
Sign up to set email alerts
|

Adipophilin as prognostic biomarker in clear cell renal cell carcinoma

Abstract: ObjectiveTo study the expression of adipophilin (PLIN2), a lipid storage-associated cell protein, in different subtypes of renal cell cancer and to elucidate its prognostic value.Materials and MethodsTwo-hundred-seventy-five patients with renal cell carcinoma (RCC) were included in this study. Immunohistochemistry with a polyclonal antibody to adipophilin was used on the tissue microarray (formalin-fixed, paraffin-embedded tissue) for detection of adipophilin. Median follow-up time was 91 (range 1-159) months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…The present results revealed that high PLIN2 expression was associated with good OS (P<0.001) and DFS (P=0.0006), and may be considered a diagnostic biomarker in patients with ccRCC with various clinicopathological characteristics. Three previous studies also concluded that increased PLIN2 mRNA expression is associated with a satisfactory cancer-specific survival in patients with ccRCC ( 32 , 33 , 44 ) and metastatic lesions exhibited low expression ( 32 , 44 ). Notably, the present study demonstrated that knockdown of PLIN2 promoted ccRCC cell invasion and migration in vitro .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The present results revealed that high PLIN2 expression was associated with good OS (P<0.001) and DFS (P=0.0006), and may be considered a diagnostic biomarker in patients with ccRCC with various clinicopathological characteristics. Three previous studies also concluded that increased PLIN2 mRNA expression is associated with a satisfactory cancer-specific survival in patients with ccRCC ( 32 , 33 , 44 ) and metastatic lesions exhibited low expression ( 32 , 44 ). Notably, the present study demonstrated that knockdown of PLIN2 promoted ccRCC cell invasion and migration in vitro .…”
Section: Discussionmentioning
confidence: 89%
“…Notably, the majority of these tumors have clear cell histology ( 30 , 31 ). Two major studies revealed the prognostic value of the transcript and protein levels of PLIN2 in ccRCC ( 32 , 33 ). Furthermore, a recent study provided evidence to suggest that PLIN2 is upregulated in ccRCC and directly proportional to hypoxia-inducible factor (HIF)2α activation ( 34 ); however, to the best of our knowledge, a functional analysis of PLIN2 in ccRCC has not yet been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Although AQP1 is abundantly expressed in the apical membrane of proximal tubule cells, it is also known to be upregulated in lung and brain tumors . In contrast, PLIN2 is involved in lipid metabolism, transport and cellular signaling, and has been shown to be elevated in multiple malignancies that show clear cell pathology, including clear cell RCC . The exact mechanisms by which these markers are passed into the urine are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 In contrast, PLIN2 is involved in lipid metabolism, transport and cellular signaling, 24 and has been shown to be elevated in multiple malignancies that show clear cell pathology, 24,25 including clear cell RCC. 26 The exact mechanisms by which these markers are passed into the urine are unclear. Although the association of RCC with the proximal tubule provides a mechanism for these markers to be expressed in the urine, it is unclear whether they are secreted or merely shed into the urinary system.…”
Section: Discussionmentioning
confidence: 99%
“…Visualization of LDs best be facilitated by the immunohistochemical expression of adipophilin, a vehicle of small LDs in non-adipogenic cells [ 8 ]. The role of adipophilin in cancer was recently investigated, and it was found to be not only a diagnostic marker, but also an independent poor prognostic marker for certain cancers, including clear cell renal cell carcinoma and brain glioma [ 9 , 10 ]. However, studies about the prognostic value of adipophilin in lung cancer were limited, and the association between the adipophilin and hypoxic ischemic pathways remains unclear.…”
mentioning
confidence: 99%